Systematic review and meta-analysis on the therapeutic reference range for escitalopram: Blood concentrations, clinical effects and serotonin transporter occupancy - Eichentopf, Luzie; Hiemke, Christoph; Conca, Andreas; Engelmann, Jan; Gerlach, Manfred; Havemann-Reinecke, Ursula; Hefner, Gudrun; Florio, Vincenzo; Kuzin, Maxim; Lieb, Klaus; Reis, Margareta; Riemer, Thomas G.; et al. (Frontiers in Psychiatry, 2022)
INTRODUCTION: A titration within a certain therapeutic reference range presupposes a relationship between the blood concentration and the therapeutic effect of a drug. However, this has not been systematically investigated for escitalopram. Furthermore, the recommended reference range disagrees with mean steady state concentrations (11 – 21 ng/ml) that are expected under the approved dose range (10 – 20 mg/day). This work systematically investigates the relationships between escitalopram dose, blood levels, clinical effects, and serotonin transporter occupancy. METHODS: Following our previously published methodology, relevant articles were systematically searched and reviewed for escitalopram. RESULTS: Of 1032 articles screened, a total of 30 studies met the eligibility criteria. The included studies investigated escitalopram blood levels in relationship to clinical effects (9 studies) or moderating factors on escitalopram metabolism (12 studies) or serotonin transporter occupancy (9 studies). Overall, the evidence for an escitalopram concentration/effect relationship is low (level C). CONCLUSION: Based on our findings, we propose a target range of 20-40 ng/ml for antidepressant efficacy of escitalopram. In maintenance treatment, therapeutic response is expected, when titrating patients above the lower limit. The lower concentration threshold is strongly supported by findings from neuroimaging studies. The upper limit for escitalopram`s reference range rather reflects a therapeutic maximum than a tolerability threshold, since the incidence of side effects in general is low. Concentrations above 40 ng/ml should not necessarily result in dose reductions in case of good clinical efficacy and tolerability. Dose-related escitalopram concentrations in different trials were more than twice the expected concentrations from guideline reports.